2017
DOI: 10.2147/opth.s145945
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of visual outcomes after bilateral implantation of a diffractive trifocal intraocular lens and blended implantation of an extended depth of focus intraocular lens with a diffractive bifocal intraocular lens

Abstract: PurposeThe purpose of this study was to compare the visual outcomes and subjective visual quality between bilateral implantation of a diffractive trifocal intraocular lens, Alcon Acrysof IQ® PanOptix® TNFT00 (group A), and blended implantation of an extended depth of focus lens, J&J Tecnis Symfony® ZXR00 with a diffractive bifocal intraocular lens, J&J Vision Tecnis® ZMB00 (group B).MethodsThis prospective, nonrandomized, consecutive, comparative study included the assessment of 40 eyes in 20 patients implante… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
85
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(101 citation statements)
references
References 25 publications
(35 reference statements)
12
85
1
3
Order By: Relevance
“…The clinical results of this asymmetrical implantation showed excellent uncorrected visual acuities, with mean binocular UDVA (6 m), UIVA (66 cm), and UNVA (40 cm) values of -0.06 ± 0.08, 0.00 ± 0.07, and 0.05 ± 0.08 logMAR, respectively. Similarly, de Medeiros et al 13 compared the visual outcomes after bilateral implantation of a diffractive trifocal PanOptix TNFT00 IOL to visual results after blended implantation of the EDOF Tecnis Symfony ZXR00 IOL and a diffractive bifocal Tecnis ZMB00 IOL with +4.00 D near addition (20 patients, 30 to 180 days postoperatively). The authors reported that the blended group showed statistically significantly better mean binocular UDVA (-0.10 ± 0.15 logMAR) results than the bilateral group (0.01 ± 0.04 logMAR) when measured at 4 m. In contrast, the bilateral group showed statistically significantly better binocular UIVA (60 cm) and UNVA (40 cm) results, with mean values of 0.14 ± 0.05 and -0.03 ± 0.04 logMAR, respectively, compared to mean UIVA and UNVA values of 0.20 ± 0.05 and 0.11 ± 0.07 logMAR, respectively, in the blended group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The clinical results of this asymmetrical implantation showed excellent uncorrected visual acuities, with mean binocular UDVA (6 m), UIVA (66 cm), and UNVA (40 cm) values of -0.06 ± 0.08, 0.00 ± 0.07, and 0.05 ± 0.08 logMAR, respectively. Similarly, de Medeiros et al 13 compared the visual outcomes after bilateral implantation of a diffractive trifocal PanOptix TNFT00 IOL to visual results after blended implantation of the EDOF Tecnis Symfony ZXR00 IOL and a diffractive bifocal Tecnis ZMB00 IOL with +4.00 D near addition (20 patients, 30 to 180 days postoperatively). The authors reported that the blended group showed statistically significantly better mean binocular UDVA (-0.10 ± 0.15 logMAR) results than the bilateral group (0.01 ± 0.04 logMAR) when measured at 4 m. In contrast, the bilateral group showed statistically significantly better binocular UIVA (60 cm) and UNVA (40 cm) results, with mean values of 0.14 ± 0.05 and -0.03 ± 0.04 logMAR, respectively, compared to mean UIVA and UNVA values of 0.20 ± 0.05 and 0.11 ± 0.07 logMAR, respectively, in the blended group.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies assessing the clinical performance of the IC-8 IOL were also in accordance with our results. 13,17,18 Dick et al 19 found monocular uncorrected UDVA (4 m), UIVA (67 cm), and UNVA (40 cm) values of 0.06 ± 0.15, 0.08 ± 0.12, and 0.18 ± 0.14 logMAR, respectively (105 patients, 6-month follow-up). When combined with an aspheric monofocal IOL, the binocular distance-corrected defocus curve revealed a visual acuity of 0.20 logMAR or better ranging from +1.00 to -2.00 D.…”
Section: Discussionmentioning
confidence: 99%
“…Hence these lenses boast less light loss (~16% vs 18%, although unlikely to be clinically significant) than single spacing/height diffractive patterns. Trifocals have been shown to provide better visual acuity than biofocal IOLs at intermediate distances (de Medeiros et al, 2017;Vilar et al, 2017). The most recent iteration is a quadrifocal optic (diffractive step heights giving focal planes at 40 cm, 60 cm, and 120 cm), although it is stated as acting as a trifocal IOL (Kohnen, 2015;Kohnen et al, 2017).…”
Section: Multifocal Iolsmentioning
confidence: 99%
“…The studies hitherto suggest it provides visual benefits across all distances after cataract surgery, with a minimal level of disturbing photic phenomena and high levels of patient satisfaction (Cochener and Concerto Study, 2016;Kaymak et al, 2016). Compared to modern diffractive trifocal IOLs, however, it provides generally an equivalent or slightly better visual acuity at distance, but a reduced level of vision at near and only equivalent contrast sensitivity and (low) levels of dysphotopsia (de Medeiros et al, 2017;Monaco et al, 2017;Pedrotti et al, 2016;Ruiz-Mesa et al, 2017a;Ruiz-Mesa et al, 2017b).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…As such, it is believed that EDOF IOLs may work less efficiently for near vision compared to some multifocal IOLs. [9][10][11] Several investigators have suggested that aiming for emmetropia in the dominant eye and a slightly myopic refraction ranging between 0.5 and 0.75 D in the nondominant eye may improve near vision and thereby increase patient satisfaction with EDOF IOLs. 6,12 Although good postoperative near visual acuity has been reported with this approach, the desired spherical equivalent in each eye to achieve optimum visual outcomes across all ranges is unknown.…”
Section: Introductionmentioning
confidence: 99%